Designs for Learning - A Theoretical Perspective - Staffan Selander (Stockholm University Press, 2008)
In this article, I will introduce a perspective on learning as complex processes of transformations of signs, by way of modes and media in different institutional settings. I will also discuss a design theoretic perspective in relation to different framings of knowledge and learning practices.